Potential for Sulfate Reduction in Mangrove Forest Soils: Comparison between Two Dominant Species of the Americas - Balk, Melike; Keuskamp, Joost A.; Laanbroek, Hendrikus J. (Frontiers in Microbiology, 2016)
Avicennia and Rhizophora are globally occurring mangrove genera with different traits that place them in different parts of the intertidal zone. It is generally accepted that the oxidizing capacity of Avicennia roots is larger than that of Rhizophora roots, which initiates more reduced conditions in the soil below the latter genus. We hypothesize that the more reduced conditions beneath Rhizophora stands lead to more active sulfate-reducing microbial communities compared to Avicennia stands. To test this hypothesis, we measured sulfate reduction traits in soil samples collected from neighboring Avicennia germinans and Rhizophora mangle stands at three different locations in southern Florida. The traits measured were sulfate reduction rates in flow-through reactors (FTR’s) containing undisturbed soil layers in the absence and presence of easily degradable carbon compounds, copy numbers of the dsrB gene, which is specific for sulfate-reducing microorganisms, and numbers of sulfate-reducing cells that are able to grow in liquid medium on a mixture of acetate, propionate and lactate as electron donors. At the tidal locations Port of the Islands and South Hutchinson Islands, steady state sulfate reduction rates, dsrB gene copy numbers and numbers of culturable cells were significantly higher at the A. germinans than at the R. mangle stands, although not significantly for the numbers at Port of the Islands. At the non-tidal location North Hutchinson Island, results are mixed with respect to these sulfate reduction traits. At all locations, the fraction of culturable cells were significantly higher at the R. mangle than at the A. germinans stands. The dynamics of the initial sulfate reduction rates implied a more in situ active sulfate reducing community at the intertidal R. mangle stands. It was concluded that in agreement with our hypothesis R. mangle stands accommodate a more active sulfate-reducing community than A. germinans stands, but only at the tidal locations. The differences between R. mangle and A. germinans stands were absent at the non-tidal, impounded location.